Guidance on left bundle branch pacing using continuous pacing technique and changes in lead V1 characteristics under real-time monitoring - Zheng, Nan; Jiang, Longfu; Shen, Jiabo; Zhong, Jinyan (Frontiers in Cardiovascular Medicine, 2023)
Background The changes in the morphology and characteristics of the V1 leads during left bundle branch capturing still need to be fully understood. Objective This study aims to provide some suggestions about the LBB capture process through the morphology and characteristics of the V1 lead. Method LBBP using the continuous pacing and morphology monitoring technique during screw-in using a revolving connector (John Jiang's connecting cable). The morphology and features of V1 leads are recorded by continuous monitoring technology. Results The most common morphology in the LVSP stage is QR, while in the NS-LBBP (low output) stage and the NS-LBBP (lower output) stage, it is rSR. In the S-LBBP stage, it is rsR. The predominant morphology is with r/R waves in S-LBBP, which includes variations like rSR, rsR, rSr, rsr, rR, rs, rS, and R type, making up 96.7% of the total. The r waves in lead V1 are associated with agitated myocardium conducted from the left bundle branch. Conclusion The initial r-wave in lead V1 may be a marker during the follow-up of patients with selective LBB capture.